Effects of Age and Sex on Systemic Inflammation and Cardiometabolic Function in Individuals With Type 2 Diabetes - Jody Dushay; Eva S. Rickers; Enya Wang; Jessica Gilman; Ying Zhang; Ron Blankstein; Ernest V. Gervino; Michael Jerosch‐Herold; Aristidis Veves (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Systemic inflammation, aging, and type 2 diabetes (T2D) lead to varying degrees of cardiovascular dysfunction and impaired aerobic exercise capacity. This study evaluates the impact of inflammation and sex differences on coronary and peripheral vascular function and exercise capacity in older individuals with and without T2D. Methods Older individuals (aged≥65 years) underwent biochemical and tissue inflammatory phenotyping, cardiopulmonary exercise testing, cardiovascular magnetic resonance imaging, and vascular reactivity testing. Correlation and regression analyses determined the effects of systemic inflammation, older age, and sex on cardiovascular health, stratified by T2D status. Results For the 133 recruited individuals (44% women; median age, 71±7 years, 41% with T2D), the presence of T2D most significantly increased the white blood cell count (P=0.004; P.adj.=0.140) among markers of systemic inflammation. White blood cell count was comparable in men and women. Hyperemic myocardial blood flow and flow‐mediated and flow‐independent nitroglycerin–induced brachial artery dilation were significantly impaired in men but not women with T2D. Peak oxygen consumption during exercise was lower with T2D (P=0.021), and overall reduced in women compared with men (P=0.002). Across all participants, both peak oxygen consumption during exercise and hyperemic myocardial blood flow were significantly impaired with increased white blood cell count. Women showed more adverse myocardial remodeling assessed by extracellular volume than men (P=0.008), independently of T2D status. Conclusions The pathophysiological manifestations of T2D on vascular function and aerobic exercise capacity are distinct in older men and women, and this may reflect underlying differences in vascular and myocardial aging in the presence of T2D.